Librarians Information Literacy Annual Conference (LILAC) 2016 - Larkin, Genevieve (Library Association of Ireland, 2016)
Librarians Information Literacy Annual Conference (LILAC) is organised by CILIP’s Information Literacy Group and is the biggest gathering of information literacy librarians in the UK. This year it was hosted by UCD in the O’Brien Centre for Science and some 300 delegates attended. Over three days delegates enjoyed very different keynotes, multiple workshops, papers, interactive posters, a networking evening in the Chester Beatty Library and a Conference Dinner at Royal Hospital, Kilmainham. Key themes included the role of evidence-based research in librarianship; engaging learners through games; and the strategic importance of digital literacy to library and information services.
An Leabharlann
Librarians Information Literacy Annual Conference (LILAC) 2016
Keywords: Information literacy; LILAC; Digital literacy; Library and information services; LIBRARY; Librarianship; Teaching and learning; information literacy